Electrical Power Engineering Current State, Problems and Perspectives - Ushakov, Vasily Y. (Green Energy and Technology,, 2018)
This book provides the short history, current state, main problems and historical perspective for the development of electrical power engineering. The focus of the textbook is on the two most important issues related to meeting of the growing needs of humanity in electricity: "Hunger for energy" and "Ecological infarct". In the book are discussed the methods of their solution: optimization of energy balance, use of renewable energy resources, new methods of electricity production, increase of the efficiency of production, accumulation, transmission, distribution and consumption electricity. The third issue - social and geopolitical threats due to the increasing need for energy - in the textbook is not considered inasmuch it details in non-stop regime discussed in the mass media. Choosing the structure and content of the textbook is based on the ten years of the author experience of giving lectures to Tomsk Polytechnic University students who study according t o the program Electric Power Engineering. This textbook is addresed to students, masters and post-graduates. It can be interesting for everyone who is thinking about the future of our civilization, in general, and meeting of human needs in electric power, in particular.